2011
DOI: 10.1021/nn103561u
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology Induced Localized Electric Field and Piezoresponse Enhancement in Nanostructured Thin Films

Abstract: Nanostructured piezoelectric and ferroelectric thin films are being increasingly used in sensing and actuating microdevices. In this work, we report the experimental discovery of localized electric field enhancement in nanocolumnar piezoelectric thin films and its significant impact on piezoresponse. The magnitude of electric field enhancement is associated with nonflat surface morphologies and is in agreement with theoretical and finite element models. The influence of this surface morphology induced enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Majdoub et al have analytically demonstrated that piezoelectric energy harvesting is enhanced at the nanoscale due to increased strain gradients, which scales with the feature size of nanostructures 20–22. We have also shown by a combination of experimental measurements and phase field simulations that surface nanostructure leads to piezoelectric strain and response enhancment 23. These results highlight the need for further study into the relationship between strain gradients in nanostructures and piezoelectric response.…”
Section: Resultssupporting
confidence: 87%
“…Majdoub et al have analytically demonstrated that piezoelectric energy harvesting is enhanced at the nanoscale due to increased strain gradients, which scales with the feature size of nanostructures 20–22. We have also shown by a combination of experimental measurements and phase field simulations that surface nanostructure leads to piezoelectric strain and response enhancment 23. These results highlight the need for further study into the relationship between strain gradients in nanostructures and piezoelectric response.…”
Section: Resultssupporting
confidence: 87%
“…The addition of strontium (Sr) to PZT compounds to realize strontium-doped PZT (PSZT) enhances piezoelectric and ferroelectric properties of the compound both in bulk and thin film structures [9][10][11][12][13]. Longitudinal piezoresponse (d 33 ) values as high as 892 pm/V on gold-coated silicon [13] and 1450 pm/V on platinum-coated silicon [14] are reported for the piezoelectric response of (Pb 0.92 Sr 0.08 )(Zr 0.65 Ti 0.35 )O 3 compounds under the converse piezoelectric effect. Nanomechanical properties of PZT and PSZT thin films play an important role in the functionality of the microelectromechanical systems (MEMS) and energy transduction applications that use these films.…”
mentioning
confidence: 99%
“…Full details on the sample preparation and deposition processes can be found in our earlier work [17,18]. The synthesized films exhibited strong preferential orientation with their c-axis normal to the substrate [14,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a combined computational, experimental and phenomenological effort, we identify the charging/discharging mechanism underlying the observed oscillations between circular and hexagonal nanodomain patterns in lead zirconate titanate (PZT) nanodisks driven by electron beams. Using phase-field modelling [10,14,15], we demonstrate the crucial influence of charge on the nanodomain patterns, and show that we can reproduce domain structures similar to those observed in experiment. The subhertz frequency response of the nanodomain reorientation results from relaxation oscillations [16][17][18] between threshhold charging of surface traps [19] and subsequent discharging by nanodomain wall creep [20], where quantitative agreement is made using prior measurements on PZT samples.…”
mentioning
confidence: 52%